THE CORRELATION BETWEEN SELF-REGULATED LEARNING STRATEGIES AND READING COMPREHENSION - Amrin Winata; Farnia Sari (Universitas Tridinanti Palembang, 2021)
Self-regulation is one of the motivational factors influencing the students’ learning process. It helps the students to accomplish the learning goals by formulating the thoughts and action to support the learning process. The aims of this study were to find out (1) the students Self-Regulated Learning (SRL) strategies at the eleventh graders of SMA Arinda Palembang, and (2) whether there was or not any significant correlation between SRL and reading comprehension of narrative text. The population and sample of this study was the students of eleventh grade of SMA Arinda Palembang. The total of sample was 46 students selected by using non-random sampling technique. Self-regulated learning (SRL) strategies questionnaire and reading comprehension test were administered as the instruments of study and they were distributed to the students to gather the data. In analyzing the data, correlation analysis was used. Based on the statistical analysis, it was found that the correlation coefficient or the r-value (0.631) was higher than r-table (0.245). Then, the level probability (p) significant (sig.2-tailed) was 0.000. it means that p-value (0.000) was lower than 0.05. it can be concluded that there was high significant correlation between the students’ self-regulated learning strategies and reading comprehension in narrative text. Keywords: Self-regulated learning strategies, reading comprehension